MEMAHAMI MAKNA DAN URGENSI ASBAB ANNUZUL QURAN - Herni Herni; Helda Helda; Hayatun Nida (CV. Adiba Aisha Amira, 2022)
Understanding the events of asbab an-nuzul is aimed at better understanding the verses of the Qur'an with reliable sources without the slightest doubt, because this asbab annuzul also the scholars make a reference and even exist in its preparation in a special way, because they think So important is the story of asbab an-nuzul itself, so with that we as Muslims must also know how the story of asbab an-nuzul itself is without having doubts about learning and teaching it to students.